Factors Affecting Green Banking Implementation in Indonesia - Rico Elhando Badri; Susanti SE MM; Anandha Sartika Putri (Prosiding International conference on Information Technology and Business (ICITB), 2022)
The purpose of this study is to determine the impact of green banking and financial performance on bank profitability. The population of this study included banks listed on the Indonesia Stock Exchange (IDX) for the period 2016-2021 and those that published sustainable financial statements and presented a sample of eight banks using the purposive sampling method. The data analysis technique used is multiple regression analysis with panel data. The result of this research was that Green Banking had a significant on the Bank Profitability; Bank Size had an insignificant on Bank Profitability; NPL had a significant on Profitability, and BOPO had a significant on Profitability. Keywords— Green Banking, Bank Size, NPL, BOPO, and Bank Profitability